Kinetic model for direct smelting reduction process of Huimin iron ore. (1st June 2013) - Fan, G-F; Qing, S; Wang, H; Hong, W-C
<x xml:space="preserve">Abstract</x> A series of experiments have been carried out to investigate the direct melting reduction process of high phosphorus iron in a nitrogen atmosphere with non-isothermal heating. The weight loss factor of the iron ore can be considered as a function of the temperature in the reduction progress. The kinetic parameters of the model can be determined by the data in a single test with a non-isothermal heating rate. With the temperature increasing, the reduction process can be divided into decrystal water phase of limonite, the pre-reduced phase of hematite, and finally reduced phase. The final reduction can be divided into three sections. On this basis, functions of the reaction mechanism and apparent activation energy in each stage are expected to be investigated. Then, the compensation effect of the whole reaction process is presented. Finally, the relationship of apparent activation energy and pre-exponential factor are also analysed.